The use of operational modal analysis and mode tracking for insight into polar vessel operations. (September 2021) - van Zijl, C.; Soal, K.; Volkmar, R.; Govers, Y.; Böswald, M.; Bekker, A.
Abstract: Accurate dynamic models of flexible ship structures are required to predict structural vibration caused by environmental loads. Knowledge of dynamic or modal properties are important, for example, to study fatigue damage. In this paper, operational modal analysis (OMA) is used to identify the vibration characteristics of a polar vessel from full-scale acceleration measurements. Five modes are tracked over a range of different operating and environmental conditions, including calm, open water, two ice cases and an open water storm. Compared to the calm, open water conditions, vertical bending modes were generally affected the most by the operating environment, with natural frequency and damping increasing up to 3.7 and 349 %, respectively, in ice. Severity of two-node and three-node vertical bending responses, quantified using a root-mean-square value, were found to be especially large during the open water storm case. Temporal behaviour of two-node and three-node vertical bending due to wave-slamming further contained multiple whipping responses, pointing towards possible cumulative damage over a large number of stress cycles occurring at the midship. Higher damping in ice resulted in responses with lower magnitudes and shorter durations. Highlights: Dynamic characterisation of a polar vessel through operational modal analysis. Identification of structural damping in open water and ice. Variations in modal parameters are tracked to understand structural interactions with waves and ice. High energy modal responses due to whipping are caused by wave-slamming in open water.